Inhibitory Effect of Chlorhexidine and Clove Extract Oral Rinses in Reducing Dental Plaque Microbes - Himratul-Aznita, W.H.; Zainal-Abidin, Z. (Medwell Publications, 2008)
Dental plaque is a thin film of microorganisms on the tooth surfaces and contributes to the development of dental caries and periodontal disease. It has been widely known that the usage of antimicrobial oral rinses plays an important role in maintaining oral hygiene mainly by reducing the numbers of dental plaque microbes. This study has been carried out with the aim of comparing the clinical effectiveness of Chlorhexidine (CHX) (Oradex®) and commercialized clove extract (Mustika Ratu®) oral rinses in reducing dental plaque microorganisms. In addition, the aim was also to determine the duration of effects and magnitude of suppression of plaque microbes with the usage of the oral rinses. The antibacterial effects of CHX and clove extract oral rinses of dental plaque microbes were evaluated in healthy adults, which were not on any antibiotic treatment for the past 6 months. The oral rinses were tested on volunteers for a period of 30 min interval for up to 120 min. Volunteers were required to suspend normal oral hygiene habits and on the sampling day, the tooth surfaces of each volunteer were swabbed, followed by rinsing with the specified oral rinse. The tooth surfaces were swabbed again after 30, 60 and 120 min. Swab samples were serially diluted and plated on BHI agar. Phenotypic appearance and the colony forming units (CFU mL 1) were obtained. Results indicated that bacterial colony formation was significantly inhibited by both oral rinses and exhibited similar levels of antibacterial activity. However, the oral rinse containing CHX exhibited a longer duration of activity in controlling oral microbes compared to clove extract oral rinse. In conclusion, CHX has a better antimicrobial action to reduce and exhibit longer magnitude of suppression of dental plaque microbes than clove extract oral rinse.